Association between Vitamin D receptor (VDR) gene polymorphisms and hypertensive disorders of pregnancy: a systematic review and meta-analysis - Guo,Yicong; Zhang,Yu; Tang,Xiangling; Liu,Xionghao; Xu,Huilan (PeerJ, 2023)
Background Hypertensive disorders of pregnancy (HDP) are currently one of the major causes of pregnancy-related maternal and fetal morbidity and mortality worldwide. Recent studies provide evidence that maternal Vitamin D receptor (VDR) gene polymorphisms probably play a key role by affecting the biological function of vitamin D in some adverse pregnancy outcomes, while the relationship between the VDR gene polymorphisms and the risk of HDP remains controversial in current studies. This systematic review and meta-analysis aimed to comprehensively evaluate the association of the VDR gene polymorphisms with HDP susceptibility. Methods This meta-analysis follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and a protocol has been registered in the PROSPERO (ID: CRD42022344383) before commencing this review. PubMed, Web of Science, Embase, and the Cochrane Library databases were searched until January 21, 2023. Case-control and cohort studies that reported the association of the VDR gene polymorphisms with HDP were included. The quality of the included studies was assessed using the Newcastle-Ottawa Scale (NOS) for non-randomized studies. The odds ratios (ORs) with corresponding 95% confidence intervals (CIs) of the five models (allele model, dominant model, recessive model, homozygous model, heterozygous model) were pooled respectively, and subgroup analysis was performed based on ethnicity. Results A total of ten studies were included. The VDR gene ApaI polymorphism was associated with HDP susceptibility in the dominant model (OR: 1.38; 95% CI [1.07–1.79]; P = 0.014) and the heterozygote model (OR: 1.48; 95% CI [1.12–1.95]; P = 0.006). In subgroup analysis, the heterozygote model (OR: 2.06; 95% CI [1.21–3.52]; P = 0.008) of the ApaI polymorphism was associated with HDP in Asians, but not in Caucasians. Conclusion The VDR gene ApaI polymorphism may be associated with HDP susceptibility. Insufficient evidence to support the existence of ethnic differences in this association.
Keywords: Vitamin D receptor; Polymorphisms; Hypertensive disorders of pregnancy; Gestational hypertension; Preeclampsia; Systematic review; Meta-analysis